Skin cancer knowledge, attitudes, beliefs, and prevention practices among medical students: A systematic search and literature review - V.K. Nahar, MD, PhD, MS; A.H. Wilkerson, PhD; G. Ghafari, MPH; B. Martin, BS; W.H. Black, MD; J.F. Boyas, PhD; M. Savoy, PhD; G. Bawa, MS; F.C. Stafford, Jr, DO; M. Scott, BSN, RN; T.B. Grigsby, BS; Z. Gromley, PhD; et al. (Wolters Kluwer, 2018)
Background: As future physicians, medical students will play an important role in the prevention of skin cancers by becoming directly involved in skin cancer prevention education and counseling patients about the hazards of ultraviolet light. Objective: We assessed the skin cancer-related knowledge, attitudes, beliefs, and prevention practices reported in previous studies of medical students. Methods: The search for relevant articles was performed in four electronic databases: PubMed (Medline), Cumulative Index to Nursing and Allied Health, ERIC, and PsycINFO. Studies were included if they met the following criteria: 1) targeted medical students; 2) assessed sun avoidance, sun protection, skin self-examination, and/or indoor tanning behaviors; 3) were published in peer-reviewed journals; and 4) complete data were available for extraction. Results: A total of 21 studies are included in this review. Important findings include moderate-to-high levels of skin cancer knowledge and low levels of both sunscreen and ultraviolet light knowledge. The attitudes and knowledge of medical students reflect a low level of concern with regard to the perceived importance of skin cancer compared with other forms of cancer despite a high level of concern for the importance of skin cancer prevention. Furthermore, this review demonstrated that medical students fail to protect themselves routinely from the sun and have a high interest in tanning bed use. Conclusion: This review demonstrates the need to educate medical students about skin cancer and skin cancer preventive behaviors. New strategies and educational campaigns should be developed to communicate better information on skin cancer morbidity, mortality, and prevention to medical students. This will pay dividends by improving the practice of these future physicians in all specialties.